Expression of FGFR-2 and FGFR-3 in the normal human fetal orbit. Issue 12 (18th November 2005) - Khan, S H; Britto, J A; Evans, R D; Nischal, K K
Abstract : Aims: To demonstrate the expression patterns of two fibroblast growth factor receptors (FGFR-2 and FGFR-3) in the normal human fetal orbit. Methods: 6 μm orbital slide sections were prepared from 12 week old human fetal material obtained within established ethical guidelines. Radioactive in situ hybridisation techniques were used to demonstrate the expression patterns of FGFR-2 and FGFR-3 within these sections. Only one foetus had appropriate orbital sections taken. Results: FGFR-2 was expressed within the extraocular muscles (EOMs) and the optic nerve sheath and to a lesser degree within the orbital periosteal margins and the cranial sutures. FGFR-3 was expressed a lot within the periosteal margins and cranial sutures but not within either the EOMs or the optic nerve sheath. Conclusions: FGFR-2 and FGFR-3 are differentially expressed within different orbital components. FGFR-2 gene mutations may be responsible for craniosynostotic syndromes such as Crouzon, Pfeiffer, and Apert, while those in the FGFR-3 gene may cause isolated unicoronal synostosis. EOMs may be histologically abnormal in cases of Apert, Pfeiffer, and Crouzon syndromes but not isolated unicoronal synostosis. The pattern of expression of FGFR-2 in the normal human fetal orbit may explain some of the EOM histological findings seen in some cases of Apert, Pfeiffer, and Crouzon syndromes.